An Intensive Study of Finite Dimensional Hesitant Fuzzy Normed Linear Spaces - Krishnamoorthy, Kavitha; Muralikrishna, Prakasam (Iraqi Journal of Science, 2025)
The author's previous covered the concept of fuzzy normed linear space into hesitant fuzzy normed linear space. This work introduces hesitant fuzzy n-normed linear space as a generalization of n-normed space in addition to the generic t-norm, which is the major objective, and provides an expanding family of S*-n-norms that correspond to fuzzy n-norms. The decomposition theorem of a hesitant fuzzy norm into a set of crisp norms has been proven to fail when a t-norm other than "min" is used. This paper also addresses essential conclusions for fuzzy normed linear spaces of limited dimensions within a broad t-norm framework.